Islamic tourism: The impacts to Malaysia’s tourism industry - Kamarudin, Lina Munirah; Nizam, Hairul (2013)
This paper seeks to explore the evolution of Islamic tourism in the world especially in Malaysia as a multi-cultural nation. Since the religious factors have been brewed in Islamic tourism, it most likely influences the pros and cons of its growth in Malaysia. The data gathered from literature review were critically debated to fill the gaps in understanding the emergence of Islamic tourism. Therefore, the main issue address in this paper is to highlight as to how Islamic tourism (or so called religious/spiritual tourism) could give significant changes and impacts towards Malaysia’s tourism industry. The findings of the study provide the impacts of Islamic tourism from the aspects of economics, socio-culture, politics and environment. Since the tourism industry itself is a profitable chain, it also helps to be as a weapon of poverty reduction to Muslim countries while preserving and conserving the Islamic socio-culture. Islamic tourism helps to stabilize the politic issues and provide less pollution to the environment.